Pengaruh Risiko Likuiditas dan Solvabilitas Terhadap Profitabilitas Pada Perusahaan Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Kismi Mahmudha Siwi (Universitas Katolik Widya Karya Malang, 2023)
This study aims to analyze the effect of liquidity (current ratio and cash ratio) and solvency (Debt to Equity Ratio or DER) on profitability (Return on Assets or ROA). This research was conducted with quantitative methods. The population in this study are pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample used in this study were 10 companies selected by purposive sampling method. The data analysis method used is multiple linear regression method performed with SPSS 25. The results of this study indicate that: (1) the F test simultaneously shows the variables current ratio, cash ratio, and DER have a positive effect on ROA; (2) the t test shows that partially the current ratio and DER variables have no effect on ROA and the cash ratio variable has an effect on ROA; (3) the R2 test shows that the Adjust R value is 0.658 meaning that the current ratio, cash ratio, and DER variables can explain the ROA of 65.8% and the remaining 34.2% is influenced by other variables.